Die Übersetzung eines heiklen Konzepts: „Rasse“ in Fukuzawa Yukichis Sekai kunizukushi - Merida, Tarik (Bunron, 2021)
The aim of this paper is to retrace the early history of the concept of “race” in Meiji Japan (1868-1912). Similar to numerous other new concepts that were imported in the process of the Meiji Restoration, “race” was also translated into the Japanese language. It was, however, not merely a lexical matter: it meant translating a hegemonic discourse, that under the cover of scientific legitimation was offering a rationale for imperialism. Obviously on the losing side of this discourse, the Japanese translators engaged with it faced a dilemma: “Race” was, after all, part of the “modern” Western knowledge that was eagerly being imported. Yet, it also implicated the inferiority of the Japanese. The Meiji thinker Fukuzawa Yukichi (1835-1901) managed, through a process of translation and adaptation, to resolve this dilemma by rejecting the determinism implied by the notion of “race” without negating the existence of differences between humans. Thereby, he asserted that the Japanese were able to reach the level of civilization displayed by the Western powers.